Representasi Feodalisme Pesantren dalam Media Televisi: Analisis Pemberitaan Trans7 dan Realitas Sosial di Pesantren An-Nur 2 Bululawang Malang - Rohanita, Lailatur; Husen, Kemal; Romadhon, Mochamad Rizqy; Nisak, Alfatun; Mufarrohah, Lailatul; Abrori, Ali Mukhammad (Lembaga Yasin AlSys, 2025)
Pesantren feudalism as an issue of media representation has increasingly come to the fore in line with the widening gap between dramatized news coverage and the everyday realities of pesantren communities, particularly amid digital disruption that drives sensational narratives at the expense of factual accuracy. This study examines the media representation of pesantren feudalism in Trans7 news coverage and compares it with the social reality at Pesantren An-Nur 2 Bululawang, with the aim of analyzing how a feudal image is constructed in television reporting and how this construction intersects with, and often contradicts the educational, ethical, and cultural dynamics practiced within the pesantren. Using a qualitative approach with a case study design, data were obtained through broadcast document analysis, observation of the pesantren environment, and in-depth interviews with caregivers, ustaz, and santri, and subsequently analyzed interpretively. The findings reveal three main patterns of media representation: symbolic dramatization of authority, selective emphasis on hierarchical relations, and visual framing that reinforces feudal stereotypes of pesantren. Conversely, field data show that authority in the pesantren is ethical, contextual, and pedagogical in nature, embodied through the principles of adab, ta’dzīm, mutual respect, and dialogical learning processes, while also uncovering negative data or anomalies related to variations in disciplinary practices and differences in understanding among santri. The study concludes that media narratives tend to oversimplify pesantren traditions and fail to capture their complexity as dynamic Islamic educational institutions. The implications of these findings enrich scholarship on media representation and the culture of Islamic education, while encouraging journalists, policymakers, and pesantren leaders to foster more accurate, ethical, and constructive public communication about the pesantren world.